2020
DOI: 10.1002/ejhf.1769
|View full text |Cite
|
Sign up to set email alerts
|

Composite trends of cardiogenic shock complicating acute myocardial infarction

Abstract: This article refers to 'Trends in cardiogenic shock complicating acute myocardial infarction' by N. Aissaoui et al., published in this issue on pages 664-672.Cardiogenic shock (CS) is the leading cause of death in patients with acute myocardial infarction (AMI), with in-hospital mortality as high as 40-50%. [1][2][3][4][5][6][7][8][9][10][11][12] Although improved AMI care had significantly reduced the incidence of CS in the early 2000s, more recent observational studies showed varying trends with a decreased,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In the last 20 years, most of the cohorts report a 40–60% in‐hospital or 30 day mortality. 19 This occurs despite the widespread use of emergent coronary revascularization in the context of AMICS. The SHOCK trial showed a trend towards improvement in 30 day mortality and a significant reduction in 6 month mortality among patients with AMICS undergoing urgent revascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 20 years, most of the cohorts report a 40–60% in‐hospital or 30 day mortality. 19 This occurs despite the widespread use of emergent coronary revascularization in the context of AMICS. The SHOCK trial showed a trend towards improvement in 30 day mortality and a significant reduction in 6 month mortality among patients with AMICS undergoing urgent revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…AMICS is an entity associated with high mortality. In the last 20 years, most of the cohorts report a 40–60% in‐hospital or 30 day mortality 19 . This occurs despite the widespread use of emergent coronary revascularization in the context of AMICS.…”
Section: Discussionmentioning
confidence: 99%
“…AMI is a critical disease of coronary atherosclerosis, with its major pathogenic factor being secondary thrombosis caused by the rupture and erosion of unstable plaques in the coronary artery. This results in coronary occlusion and myocardial ischemia and necrosis [9] . Visfatin, a type of adipocytokine, has multiple biological effects and is closely associated with the occurrence and development of hypertension, heart failure, and coronary heart disease according to a large amount of research evidence in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the introduction of myocardial revascularisation therapy and an overall improvement in mechanical reperfusion strategies [ 2 , 3 , 4 ], CS remains the leading cause of in-hospital death in patients with AMI, with an in-hospital and 1-year mortality rate of 40% and 50%, respectively [ 5 ]. Some recent registries reported an increased mortality rate, which may be related to changes in the mean age and risk profiles of CS patients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%